Sistem Hidroganik pada Kelompok Wanita Tani guna Meningkatkan Hasil Panen dan Menunjang Ketahanan Pangan di Kawasan Perumahan - Lian Agustina Setiyaningsih; Sri Widayati; Laksni Sedyowati; Muhammad Alwi Risqillah; Sufiyanto; Diyah Sukanti Cahyaningsih (I-Com: Indonesian Community Journal, 2023)
This service aims to increase the harvest yields of the Green Cemara Farm Women's Group in Malang City and support food security in urban settlements. The combination of residential communities, empowerment, and sustainable agriculture presents an exciting path to addressing this pressing issue. Empowering housing communities through the application of hydroorganics offers a transformative approach to overcoming challenges. Problems with production partners selling organic vegetables and fulfillment for housing residents. The implementation method goes through four stages, namely: identification of problems and needs, program design, implementation and evaluation. The activities carried out are creating a hydroorganic system and carrying out planting using hydroganic media. Then carry out hydroorganic training so that harvest results are effective. As hydroganic practices grow in popularity around the world, this dedication underscores their important role in improving food security, encouraging sustainable urban agriculture, and encouraging the empowerment of residential communities. The results reflect the potential for expanding the hydroorganic movement to engage more residential residents and address contemporary food security challenges.